Stingless Bee Propolis Review as Biocosmetics for Anti-Acne, Anti-Aging, and Skin-Whitening - Paramita Swandari; Toruan Vera Madonna Lumban; Rahma Khairunnida; Zubaidah Mona; Arung Enos Tangke; Kusuma Irawan Wijaya (Journal of Apicultural Science)
Data on cosmetic sales has grown significantly recently, with consumers increasingly choosing natural cosmetics or biocosmetics. The natural ingredient that has received attention recently is stingless bee propolis. Stingless bee propolis has been utilized in cosmetics manufacturing and has been extensively studied for its beneficial properties for the skin, including anti-acne, anti-aging, and skin-whitening properties. This review comprehensively analyzes the potential of stingless bee propolis for anti-inflammatory, anti-bacterial, antioxidant, anti-wrinkle, anti-melanogenesis, and sunscreen activity. The chemical compound that has been found in stingless bee propolis and can be used in biocosmetics, including p-coumaric acid, gallic acid, caffeic acid, ellagic acid, ferulic acid, catechin, quercetin, apigenin, kaempferol, glyasperin, broussoflavonol, rutin, methyldiplacone, nymphaeol, geranyl flavonol, oleic acid, palmitic acid, ascorbic acid, and tocopherol. The potential applications of stingless bee propolis in biocosmetics are significant, and there are numerous benefits of using it. Further research is needed to understand its potential applications and benefits for the skin.